Motion events in Afrikaans: their expression by adult speakers and by children with and without language impairment - Oosthuizen, Helena; Höhle, Barbara; Southwood, Frenette (Stellenbosch Papers in Linguistics Plus, 2011)
Motion events occur frequently in everyday life as people and objects constantly change their relative location to one another. Although children's descriptions of motion events resemble those of adults in their own language group from very early on (Choi and Bowermann 1991), there is increasing evidence for subtle differences as well. Young children speaking different languages seem to have some difficulty in expressing two types of spatial information in the same conceptual frame (e.g. Ochsenbauer and Hickmann 2010). In English and other satellite-framed languages such as German and Afrikaans, this task involves using a complex particle verb construction in which a directional particle (e.g. out) combines with a prepositional phrase carrying further information about the source or goal of movement (e.g. some bees came out of the tree) (Berman and Slobin 1994:161). Little is known about the development of this type of structure in satellite-framed languages such as Afrikaans. This paper examined whether (i)  there are developmental differences between adults and 6-year-old Afrikaans-speaking children in the production of preposition+verb particle structures, and whether (ii) children with language impairment produce these structures in a different way than typically developing children. Target elements were preposition+verb particle structures with the particles af 'down', in 'in', uit 'out' and op 'up'. The performance of ten adults was compared to that of 30 typically developing and three language-impaired 6-year-olds. Half of the participants in the adult and typically developing groups were speakers of Mainstream Afrikaans (MA), and half were speakers of Cape Afrikaans (CA), a non-mainstream dialect. Distinct developmental differences that could not be attributed to dialectal variation, were found between 6-year-olds and adults. Children with language impairment showed less variation in their responses than their typically developing peers. Possible explanations for the findings are discussed.